Determinant of Water Quality and Suitability of River Ethiope for Fish Survival in Southern Nigeria - Ochuko, Ushurhe; Thaddeus, Origho; John, Ewhuwhe-Ezo (Canadian Journal of Agriculture and Crops, 2016)
The study examines the quality of water and suitability of River Ethiope for fish survival in Southern Nigeria. It is an empirical research work that involved field collection of water samples from six sampled sites along the course of River Ethiope and laboratory analysis of the water samples collected. The results showed that variation exists in the physico-chemical and biological parameters of the analyzed water samples. Also, some of the parameters examined such a pH, conductivity, temperature, turbidity, DO, TSS, hydrocarbon, Mg, Fe, Ca, among others are satisfactory and falls within the approved standard requirement for fish survival. While parameters such as BOD, ammonia, nitrate, COD, chloride and zinc concentrations were above the recommended amount for fish survival. However, the quality of water from River Ethiope does not differ significantly from approved standard for fish survival at P>0.05; hence, the water from the river is good for fish breeding and fish survival. Routine monitoring of human activities along the course of the river and periodic testing of the water be carried out to identify impairments and help check the increase in the concentration of physico-chemical and biological indices of the water in order to address issues of fish kills and boost fish production for man’s consumption.